3D Nanotomography of calcium silicate hydrates by transmission electron microscopy. Issue 4 (7th December 2020) - Viseshchitra, Panod; Ercius, Peter; Monteiro, Paulo J. M.; Scott, Mary; Ushizima, Daniela; Li, Jiaqi; Xu, Ke; Wenk, Hans‐Rudolf
Abstract: Calcium silicate hydrate (C‐S‐H), is the principal hydration product of Portland cement that mainly contributes to the physical and mechanical properties of concrete. This paper aims to investigate the three‐dimensional structure of C‐S‐H with Ca/Si ratios of 1.0 and 1.6 at the nanoscale using electron tomography. The 3D reconstructions and selected region of interest analysis confirm that the morphology of both C‐S‐H materials are foil‐like structures. The difference between the two materials is the density of elongated structures. C‐S‐H with Ca/Si ratio 1.6 is clearly composed of denser particles compared to the other C‐S‐H material due to overlapping of the foil‐like structure. Pore analysis shows that C‐S‐H 1.0 and C‐S‐H 1.6 have porosities 69.2% and 49.8% respectively. Pore size distribution also reveals that C‐S‐H 1.0 has pore size range between 0‐250 nm and C‐S‐H 1.6 between 0‐100 nm. The pore network's size of C‐S‐H 1.0 is significantly larger than 1.6. This study illustrates the capability of using electron tomography to determine the 3D nanoscale structure of cementitious products and to distinguish between C‐S‐H 1.0 and 1.6.